Development of Flash Movie Learning Media with a SETS Vision to Improve Critical Thinking Skills and Learning Outcomes on Environmental Pollution Material - Ahmad Faisal Amri; Kartono Kartono (Postgraduate, University of Mataram, 2023)
This research aims to determine: the feasibility of flash movie learning media with a SETS vision for use in biology learning, the influence of flash movie learning media with a SETS vision on improving student’s critical thinking skills, and the influence of flash movie learning media with a SETS vision on improving student learning outcomes. The development procedure in this research refers to steps adapted from the Borg & Gall Model which include: collecting information, planning, developing an initial product form, conducting limited trials, carrying out revisions, conducting field trials, and carrying out revisions. The data analysis techniques used are descriptive statistics and inferential statistics using multivariate tests (MANOVA). The results of the research are as follows: The flash movie learning media has a SETS vision, from the media and material aspect it is in the